Adding a new spectral dimension to localized 1H MR spectroscopy of human prostates using an endorectal coil. Issue 2 (2003) - Thomas Thomas, M. Albert M. Albert; Binesh Binesh, Nader Nader; Yue Yue, Kenneth Kenneth; Banakar Banakar, Shida Shida; Wyckoff Wyckoff, Nathaniel Nathaniel; Huda Huda, Amir Amir; Marumoto Marumoto, Alan Alan; Raman Raman, Steve Steve
Abstract : Localized 2D shift-correlated MR spectra (L-COSY) of human prostates were recorded using an endorectal "receive" coil. Typically, 4 ml voxels were placed in the peripheral zones of the prostate. Seven healthy volunteers and one BPH patient have participated in this study so far. The total acquisition time for a 2D L-COSY was approximately 20 minutes. A 1.5 Tesla GE scanner with a body coil for RF transmission and a pelvic phased-array coil combined with a disposable rectal coil for reception was used. The 2D L-COSY spectra showed cross peaks due to citrate, spermine and occasionally choline, creatine and lipids. The 2D cross peaks due to both the multiplets of spermine were clearly resolved from choline and creatine which has been a major problem with the conventional MR spectroscopic techniques. In contrast to 2D JPRESS, improved spectral dispersion, less crowded 2D cross peaks and unequivocal detection of both multiplets of spermine were monitored in 2D L-COSY. Pilot results suggest that localized 2D L-COSY can be successfully implemented in human prostates on a clinical scanner.